Integrated rural development - The concept and its operation - Gusztav Nemes (Hungarian Academy of Sciences, Institute of Economics, 2005)
Our paper explores, on a theoretical level, the reason for frequent failures of rural development policies and identifies some potential improvements in rural policy making in Europe. Our approach to des/integration concerns actors, resources, institutions, knowledge, the fundamental logic of development, and the interplay between two distinct levels of rural development: the level of policies, or central intervention; and the level of local aspirations aimed at improving everyday rural life. Along these lines, two characteristic systems of rural development the central bureaucratic and the local heuristic can be clearly identified. Ideally, these should work in co-operation, complementing each other, forming an integrated development system, where rural policy serves to (i) channel resources, establish strategic aims and development models in a top-down mode, and (ii) convey information and mediate social, economic, political interests in a bottom-up mode. However, lack of integration and divergence of interest can lead to dysfunction, conflict and dissipation within the system. We argue that rural development policies tend to fail because the central bureaucratic system imposes top-down control and objectives throughout the development process, thus failing to sufficiently promote the reconfiguration of local resources, which is better achieved through bottom-up processes and the local heuristic system. In other words, the tendency to disjunction between the two basic socio-political systems of rural development is the main reason for the failure of rural development policy. The paper offers analytical models of integrated and non-integrated rural development systems and illustrates the argument through some examples taken from the community initiatives and the pre-accession policies of the European Union. The study is in two halves. The first half elaborates the concept of integrated rural development. based on international literature. The second part offers a few new conceptions, as a contribution to the new rural development theory and simple models of integrated and non-integrated development.
Keywords: O2; N5; P5; Q0; R0; 330; Rural development; local development; rural policy; European Union; LEADER Programme; centre-periphery; local governance